Socialization of Student’s Youth as a Factor of Development and Social Renewal of the Contemporary Society: By Experience of the Russian State Social University - Bulaev, Victor A.; Koverkina, Elena V.; Soshenko, Marina V.; Shmyrev, Viktor I.; Shmyrev, Denis V. (International Review of Management and Marketing, 2016)
The major objective of the presented work is to identify the relevance and significance of the problem on socialization of student’s youth, development of educational principles and criteria to assess the successfulness of implementation of this process in contemporary social higher education institution. The current article considers socialization as a compulsory component of the education/bringing-up process aimed at professional development as well as spiritual and moral formation of future specialists in various fields of professional activity. As a result of the study conducted on the basis of the Russian State Social University, the authors developed students’ socialization model, whose implementation in natural conditions of educational process became convincing evidence of the fact that the implementation of systematic and purposeful community-focused work promotes professional and spiritual and moral formation of personality, the development of an integral, positively oriented worldview, need for improvement and self-improvement, requirement for creative activity that offers broad opportunities for social rehabilitation and renovation of contemporary society. Keywords: Socialization, social adaptation, identification, self-actualization, self-esteem, social renewal, social improvement JEL Classifications: J240, J210, I210